ON NUCLEON-NUCLEUS SCATTERING AND THE RELATIVISTIC EIKONAL APPROXIMATION - Eiras, A.; Nemes, M. C. (Iop Publishing Ltd, 1994)
We introduce a generalization of the relativistic eikonal amplitude originally developed to describe elastic scattering between structureless particles. The coherent and incoherent proton-nucleus scattering processes are analysed and closed-form expressions for elastic and inelastic amplitudes are derived. In particular, for the incoherent case, an energy-conserving version of Glauber's theory is obtained.